Sustainable Digital Marketing Strategy for Long Term Business Growth - Maulida, Husna; Waluyo, Zahra Amany Alya; Soesanto, Harry (LifeSciFi, 2025)
In the era of rapid digital transformation and increasing market competition, businesses are challenged to move beyond short-term marketing tactics and adopt sustainable digital marketing strategies to ensure long-term growth. This study explores the essential components of a sustainable digital marketing strategy that supports enduring business success. Using a qualitative research method with a literature study approach, this article analyzes academic sources, industry reports, and relevant case studies to identify key strategic elements. The findings show that businesses must develop a deep understanding of their market and audience, maintain consistency in branding, optimize for SEO, leverage social media, implement effective content marketing, utilize data analytics, apply targeted email marketing, and invest continuously in learning and innovation. These components collectively form the foundation for sustainable digital marketing practices. The study contributes to the field by offering practical guidance for business leaders, marketers, and policymakers in designing strategies that not only drive long-term customer engagement and loyalty but also strengthen competitive positioning in a rapidly evolving digital landscape.